Erosion properties of tungsten and WTa5 alloy exposed to repetitive QSPA plasma loads below melting threshold - Makhlai, V. A.; Herashchenko, S. S.; Aksenov, N. N.; Byrka, O. V.; Garkusha, I. E.; Malykhin, S. V.; Surovitskiy, S. V.; Kulik, N. V.; Staltsov, V. V.; Lebedev, S. I.; Shevchuk, P. B.; Wirtz, M.; et al. (Kharkiv Institute of Physics and Technology, 2018)
The damage of deformed double forged pure tungsten (W) and tungsten alloyed with 5 wt.% tantalum (WTa5) have been studied in experimental simulations of ITER-like transient events (surface heat load of 0.45 MJ/m² and the pulse duration of 0.25 ms) with quasi-stationary plasma accelerator QSPA Kh-50. The plasma exposures were performed for targets maintained at room temperature and preheated at 200 or 300°C. The large and fine cracks appeared in result of plasma impacts. The high number of repetitive plasma loads below the melting threshold led to the clear degradation of thermo-mechanical properties of the affected surface layers on tungsten. Comparative analysis of the cracks propagation to the bulk is presented for both W and WTa5 samples.
Keywords: tungsten; heat load; thermo-mechanical properties; plasma loads